Depicting Prophet Muhammad (PBUH) without showing him - (:unkn) unknown (Taylor and Francis, 2021)
This chapter argues that there are important but obscured aesthetic continuities between historical artistic forms and contemporary popular cultural productions focused on the representation of Muhammad. More specifically, it draws out the genealogy between premodern textual icon and illustrated manuscript traditions with contemporary films about Muhammad, including Moustapha Akkad’s The Message and Majid Majidi’s Muhammad: The Messenger of God. As the first believers, Muhammad’s companions were eager to take him as a model for every aspect of their life. They behave just as the prophet when loving their kids, living together with their neighbors, selling or buying something, even eating, drinking, speaking, and walking. The chapter shows that the dominant practices governing artistic norms in Sunni and Shi’a communities are reflected in the ways each director depicted Muhammad. Akkad’s The Message employs strategies similar to those developed in Ottoman visual icons, while Majidi’s Muhammad: The Messenger of God mirrors visual practices of illumination and abstraction derived from miniature portraiture. © 2021 selection and editorial matter, Kristian Petersen; individual chapters, the contributors.